Psychological Dynamics of Motherless Adolescents High School Student: Case Study on High School Students in Ternate - Salwa Muin; Mu'mina Kurniawati S. J. Kahar; Rahmawati (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
This study aims to explore the psychological dynamics of adolescents who experience the loss of a mother figure (motherless) and to examine its impact on emotional, social, behavioral, and adaptive functioning. A qualitative case study approach was employed involving a 15-year-old male adolescent who had experienced maternal loss. Data were collected through observation, semi-structured interviews, and psychological assessments using the Wechsler Bellevue Intelligence Scale (WB) and the Sacks Sentence Completion Test (SSCT). The findings indicate that the loss of a mother figure had a substantial impact on the adolescent’s psychological well-being. The participant exhibited prolonged grief, feelings of loneliness, emotional insecurity, fear of losing significant family members, decreased academic motivation, and difficulties in emotion regulation. Furthermore, the adolescent demonstrated impairments in adaptive functioning, reflected in poor self-discipline, frequent tardiness at school, reduced academic engagement, and limited utilization of social relationships as sources of emotional support. Despite these challenges, the participant maintained a positive future orientation, expressed aspirations for personal success, and showed a strong desire to improve his life circumstances. The study also found that psychoeducational interventions focusing on academic motivation, growth mindset development, and positive behavioral adjustment contributed to increased emotional awareness and enhanced motivation. These findings highlight the importance of sustained emotional and psychosocial support from family members, schools, and the broader social environment to facilitate healthy psychological adjustment and resilience among adolescents coping with parental loss.